(untitled) - Niazi, Tariq H. (Philippines, 2011)
This book includes many parts: overview of the emerging legal and regulatory framework, the institutional setting for deconcentration and decentralization reforms, intergovernmental financing and recent fiscal trends, policy and planning framework for implementing reforms, critical issues for reform,...
Keywords: Finance, Public,Tài chính công; Law and legislation,Luật và pháp luật; Cambodia,Campuchia